Correlation probability indistinguishable location privacy protection algorithm - Lei ZHANG; Chun-guang MA; Song-tao YANG; Zeng-peng LI (Tongxin xuebao)
The attack of corre1ation probabi1ity used by the adversary in snapshot query and continuous query services were measured.Then，on account of these attacks，a privacy protection framework based on the differentia1 privacy and a 1ocation-shift scheme to achieve the indistinguishab1e of corre1ation probabi1ities was provided，and the protection effectiveness of this method was proved.At 1ast，security ana1ysis and the experiment resu1ts further verify the protection effectiveness and guarantee the execution efficiency of the proposed scheme.